THE PROCRASTINATION TENDENCY: A COMPARATIVE STUDY OF ACADEMIC AND NON-ACADEMIC COURSE’S LEARNERS OF AGRA CITY - Prof.Kavita Varma (International Journal of Advanced Science and Technology, 2020)
The major interest of the existing research to examine the relationship between high, average and lowgroups of procrastinators among learners of Academic and Non Academic courses from the collegesof Agra. The purposive random sampling used to collect data from 200 males and females from theage group of 19-28 years from different post-graduation and graduation courses of the Engineering,Management, Education and Science streams from various colleges in Agra. Procrastination scaleprepared by Dr. Amit Abraham used for data collection. It is a five-point scale having total 30statements. By using S.D., Mean, Anova and t-test the result derived which shows that significantdifferences are found in between Academic and Non Academic course’s learners, male and femalestudents from the whole group (N=200). 85.5% scored Average, 10% scored high and only 4.5%scored low in procrastination trait. Out of 200 college students 171 scored average, 20 high and only9 scored low procrastination